Sustainable Solution for Shoring Method of Cross-Creek Bridge in Ankeng MRT System in New Taipei City: A Case Study - Tai-Yi Liu; Cheng-An Lee; Hong-Kee Tzou; Shiun-Jye Lin; Mao-Yi Chou; Ke-Fan Jhan (International Journal of Engineering and Management Research, 2021)
In the Ankeng Light Rail MRT system (ALRMS) project, the U7 box girder passes crossing the Erbads creek and needs a temporary supporting system for the construction work. In this study, three temporary shoring system options were proposed to be the construction method. The D-B Contractor, New Asia construction and Development Corporation, evaluated and selected the optimal choice, The Steel truss frame with supporting beams, to serve as the temporary supporting system. Compare the deflection of Δmax and Δactual, which are 1.609 cm and 1.59 cm, respectively. This result presented that the shoring system composed of the H912*302*18*37 supporting beams and steel truss frame had achieved outstanding performance and work to construct the U7 box girder. This paper presents how the three options are evaluated and the detailed construction processes along with the survey verification for the method.